Quantitative analysis of risk intensity in smart grid projects in the brazilian private sector (Research, Society and Development, 2021)
This research presents a conceptual study on smart grid and risk management according to the Project Management Body of Knowledge Guide (PMBOK) v. 6.0, as well as the preparation of risk management agreement. the methodology applied was a survey used to collect data from professionals of electricity sector organizations that work on intelligent electric network projects delivered to the private sector. with the analysis of the responses, it was concluded that the project planning can be considered as a critical phase in relation to the project risk management, as it may present further complications if it is not developed in a satisfactory way, harming groups of processes such as implementation, control and monitoring and project closing. in addition, most organizations do risk management, but not always frequently, completely and effectively or still using highly reliable and diffused techniques and tools.